Volvulus of segment of ileal conduit anterior to the rectus sheath presenting as acute urinary retention - S. Bobby Viswaroop; Ganesh Gopalakrishnan (Indian Journal of Urology, 2025)
Conduit-related complications often occur late and are challenging to treat. A septuagenarian, 12 years following radical cystectomy and ileal conduit (IC) for T1G3 bladder cancer, presented with stomal stenosis which was managed by temporary placement of catheter into the conduit. One year later, he presented with no urine output from the conduit due to a double block resulting from a volvulus of the subcutaneous portion of the IC. After confirmation of the diagnosis with a computed tomography scan, the patient was managed by a reduction of the conduit length and a Turnbull stoma.